Konsep Memorabilia Sebagai Aspek Marketing pada Perancangan Interior Malang Food Center di kota Malang - Andereas Pandu Setiawan, Retno Ayu Dwipayanti (Intra, 2013)
Aspects of the history contained in the objects of memorabilia compiled as the basis for designing the restaurant to establish an atmosphere and a restaurant marketing competitiveness. Memorabilia itself has a meaning as something that is kept because it is associated with a past history. This concept aims to bring back the atmosphere that existed in 1914-1940 to the present day in the city of Malang. So the effect of that has been adapted to colonial Javanese culture and art deco style design reinforces this concept.